2017
DOI: 10.3171/2017.8.focus17447
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical applications of viscoelastic hemostatic assays

Abstract: Patients taking antithrombotic agents are very common in neurosurgical practice. The perioperative management of these patients can be extremely challenging especially as newer agents, with poorly defined laboratory monitoring and reversal strategies, become more prevalent. This is especially true with emergent cases in which rapid reversal of anticoagulation is required and the patient’s exact medical history is not available. With an aging patient population and the associated increase in diseases su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…Moreover, they can be particularly useful in patients taking novel oral anticoagulants (NOACs) and in the evaluation of PLT dysfunction induced by trauma and/or drugs [10]. In light of the above, these tests may be useful in TBI polytrauma patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they can be particularly useful in patients taking novel oral anticoagulants (NOACs) and in the evaluation of PLT dysfunction induced by trauma and/or drugs [10]. In light of the above, these tests may be useful in TBI polytrauma patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…The use of viscoelastic testing is recommended in European guidelines for managing trauma and severe perioperative bleeding, as it helps to reduce transfusion of allogeneic blood products [1,3]. Its benefits have been shown not only in trauma induced coagulopathy [3,4], but also in obstetric haemorrhage [5,6], cardiac surgery [7,8], transplantation [9], burn surgery [10], and neurosurgery [11]. Further, viscoelastic tests play a role in the diagnosis and treatment adjustment of haematological disorders like haemophilia, multiple myeloma or inherited afibrinogenemia [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, viscoelastic point-of-care coagulation testing reduces the transfusion of allogeneic blood products in trauma [ 2 , 10 ]. Previous studies also showed the benefits of its use in cardiac [ 1 , 11 , 12 ], transplant [ 13 ], neuro [ 14 ], and pediatric surgery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%